Development of Interactive Multimedia on The Subject of the Nervous System for Students Grade XI of Senior High School - Siti Nailatul Farkhah; Wachju Subchan; Mochammad Iqbal (BIOEDUKASI, 2018)
This research aimed at determining the validity of interactive multimedia on the nerve system material that had been developed and finding out the students’ response to the interactive multimedia. This was a developmental research (Research and Development) followed by a small group test on the eleventh-grade students of SMAN Ambulu totaling 9 students. The students were selected based on their ability level; 3 students with high ability level, 3 students with moderate ability level and 3 students with low ability level. The data collection techniques used were experts' validation sheets and questionnaires. The design of the interactive multimedia in this research was 4D (define, design, develop and disseminate) model developed by Thiagarajan (1974). The developmental procedure of 4D consists of 4 stages: (1) define, (2) design, (3) develop and (4) disseminate. The results showed that the validity of the developed interactive multimedia reached 82.9% according to the content expert, 86.3% based on the learning expert, 88,3% based on the learning media expert, and 82.7% based on the teacher’s (user) perspective. The results of small group test revealed that the legibility and the level of difficulty were 81.99% or in the good category, and student response score was 83.55%, it means that student had positive response toward the use of developed media in their learning. Keywords: interactive multimedia, 4D, expert validity.